2021
DOI: 10.1186/s13293-020-00348-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex and maternal postpartum depressive symptoms: findings from two prospective pregnancy cohorts

Abstract: Background Fetal sex is known to modify the course and complications of pregnancy, with recent evidence of sex-differential fetal influences on the maternal immune and endocrine systems. In turn, heightened inflammation and surges in reproductive hormone levels associated with pregnancy and parturition have been linked with the development of perinatal depression. Here, we examined whether there is an association between fetal sex and maternal depression assessed during the prenatal and postnat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…another study believed that the delivery method, such as the use of labor induction, delivery with forceps, epidural analgesia and cesarean section, is associated with an increase in the prevalence of postpartum depression [32], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…another study believed that the delivery method, such as the use of labor induction, delivery with forceps, epidural analgesia and cesarean section, is associated with an increase in the prevalence of postpartum depression [32], which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, this association is apparent in female, but not male offspring. This female-specific sensitivity appears to be linked to prenatal conditions, as others observed that male offspring are significantly associated with high postnatal, but not prenatal, maternal depressive symptoms (Cowell et al, 2021;Myers and Johns, 2019;Quarini et al, 2016). Likewise, the association between antenatal maternal depressive symptoms and child socio-emotional problems, which predict the later risk for depression, is consistently stronger in females compared with male offsprings (see Meaney, 2018 for a systematic review).…”
Section: Discussionmentioning
confidence: 91%
“… Unconscious Intrapsychic conflicts concerning pregnancy, labour and motherhood [23]  Birth of a female child, where a she was expecting a male child [5,6,14,19,24,25] . One study says the contrary, that male child is associated with PPD [26] .  Physical exhaustion: Caused by painful squeals of pelvic injuries.…”
Section: Aetiologymentioning
confidence: 97%